(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Background: Anxiety occurring in participants using AAS is probably as a result of hypothalamic pituitary gonadal axis suppression. Objectives: To know the nature and extent of anxiety associated with anabolic steroid abuse in people visiting gymnasiums. Materials and Methods: This was a cross sectional study consisting of 114 participants who are the gym going population of local gymnasiums in Delhi NCR. Tools used are: General Health Questionnaire 28, semi-structured Proforma for Socio-demographic data, and the Self Rating Anxiety Scale of Zung. Results: Male participants were found to use anabolic androgenic steroid (AAS) more commonly than females. Participants having high AAS dependence scored significantly more positive on GHQ-28. This suggested that these high scored participants suffered from other psychiatric co-morbidities as compared to non-users or nondependent users. It was observed that who were AAS dependent also suffered more from anxiety disorders as compared to non-users or non-dependent users. Conclusion: It was observed that who were AAS dependent suffered more from anxiety disorders as compared to non-users or non-dependent users.